Creación de piezas artesanales en cerámicas decorativas, utilitarias y ceremoniales basados en la cultura Cosanga de los museos de la provincia de Tungurahua, período mayo – octubre 2021 - Ruiz Bastidas, Graciela Estefanía (2023)
This work aims to create artisanal pieces in decorative, utilitarian, and ceremonial ceramics based on the Cosanga culture of the museums of the Tungurahua Province. In our country, ancestral cultures and their relics represent a fundamental role in the history of our ancestors since they show the sociopolitical, cultural, mythical, and religious structures that are part of the history of our origins. Currently, there are people who reside in the towns where they were originally established, such as in the Sucre Parish in the Patate canton of Tungurahua Province. This place is where settlements of the Cosanga culture are evident, but it needs to be given the necessary importance. The methodology used in this research is descriptive; likewise, the research method has a qualitative-quantitative approach since an investigation was carried out on the artisanal pieces in decorative, utilitarian, and ceremonial ceramics based on the Cosanga culture. Finally, the manufacturing techniques used by the Cosanga-Panzaleo potters were analyzed, as well as the physicochemical characteristics of the materiality of the white clay, which was used to create a total of 6 pieces, two decorative, two utilitarian and two ceremonial to show more about the Cosanga culture. Pieces of decorative, utilitarian, and ceremonial ceramics were made through visits to several museums in the Tungurahua Province, archaeological sites where different types of ceramics corresponding to this culture were found.